2022
DOI: 10.1007/s13346-022-01163-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of gold nanoparticles using leaf extract of Dittrichia viscosa and in vivo assessment of its anti-diabetic efficacy

Abstract: Several studies have reported the anti-diabetic effect of biologically synthesized gold nanoparticles (AuNPs). This study was designed to investigate the in vivo anti-diabetic activity of AuNPs synthesized using the leaf extract of Dittrichia viscosa in a high-fat diet (HFD)/streptozotocin (STZ)-induced diabetes in rats. AuNPs were synthesized using the leaf extract of D. viscosa, and the synthesized AuNPs were characterized by UV–visible spectrophotometer, dynamic light scattering (DLS), zeta potential, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Thus, glycemic management of diabetes remains the main target of the therapy. Consistent with previous study [40] and our past results [24,41,42], the present study confirmed that AuNPs possess a hypoglycemic effect in diabetic animal models. Several mechanisms have been suggested for the hypoglycemic effect exerted by AuNPs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, glycemic management of diabetes remains the main target of the therapy. Consistent with previous study [40] and our past results [24,41,42], the present study confirmed that AuNPs possess a hypoglycemic effect in diabetic animal models. Several mechanisms have been suggested for the hypoglycemic effect exerted by AuNPs.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have shown that it has an inhibitory effect on certain digestive enzymes, including α-amylase and α-glucosidase [44], resulting in a decrease in glucose release. Recently, we showed that AuNPs synthesized using the leaf extract of D. viscosa can alleviate hyperglycemia in high-fat diet/STZ-induced diabetes in rats, which could be by reducing hepatic gluconeogenesis by inhibiting hepatic PEPCK gene expression and activity [41].…”
Section: Discussionmentioning
confidence: 99%
“…These benefits include ease of fabrication, high entrapment efficiency, environmental friendliness, economy, stability, and repeatability. Metals and metal oxides (copper, ruthenium, silver, gold, and zinc-cerium-titanium) are the main building blocks for synthesizing and fabricating metallic nanoparticles [ [198] , [199] , [200] , [201] , [202] , [203] , [204] , [205] , [206] , [207] , [208] , [209] , [210] , [211] , [212] , [213] ]. Plant extracts can be used as reducing and stabilizing agents in nanoformulations [ [214] , [215] , [216] , [217] ].…”
Section: Metallic Nanoparticles Mediated Antidiabetic Agentsmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs) possess antioxidant and antihyperglycemic effects because of the binding of AuNPs with thioredoxin cysteine residues, which inhibits the inhibitor protein Txnip from latching to them during high glucose levels [ 108 ]. The synergistic effect of AuNPs and Dittrichia viscosa exhibits wonderful anti-diabetic properties by hindering the absorption of glucose in the intestinal villi and inhibiting the actions of α-amylase and α-glucosidase enzymes by enhancing the secretion of glucagon-like peptide 1 (GLP1) and insulin [ 109 ]. Zinc is a crucial micronutrient and zinc deficiency is positively associated with diabetes, owing to the involvement of zinc in insulin production, storage, and secretion, and it being known to improve the structural integrity of insulin [ 110 ].…”
Section: Therapeutic Potential Of Green Synthesized Nanoparticlesmentioning
confidence: 99%